Ideological and political attitudes in Yekterinoslav dioceses at the beginning of the 20th century - Savchenko, Sergiy (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
The purpose. The research intent of the study is to show the specifics of the ideological atmosphere in the Eparchy of Katerynoslav, as well as to highlight certain aspects of the relationship between the church corporation of the eparchy and imperial-patriotic organizations around the «Jewish threat».Scientific novelty. The evolution of the attitude of the Katerynoslav church community, represented by the diocesan publication, towards anti-Semitic policy is shown: from condemnation of mass violence, favorable attitude towards political and linguistic freedoms, to approval of pogroms and anti-Semitic propaganda. This evolution is connected with the post-revolutionary reaction of tsarism, which reached its apogee in 1912-1913, the church actually synchronized anti-Semitic speeches in its press with the processes of Governmental anti-Semitism.Conclusions. The anti-Semitic church campaign is directly related to serving the election campaign of extreme right-wing forces to the State Duma in 1912. At the same time, the relations of church leaders with the secular Black Hundreds («chornosotentsi») were not cloudless, positions did not coincide on many issues, in particular, the local church took a more conservative position regarding the conduct of religious freedom in society, and the Black Hundreds accused their church allies of pro-Jewish sympathies. The topic needs further research with the involvement of materials from the regional archives of southern Ukraine.